The Large-Display User Experience - Smith, Greg; Czerwinski, Mary; Robertson, George; Tan, Desney; Meyers, Brian; Robbins, Daniel; Baudisch, Patrick (Computer Graphics and Applications, IEEE, 2005)
The PC's increasing graphical-processing power is fueling a demand for larger and more capable display devices. Several operating systems have supported work with multiple displays for some time. This fact, coupled with graphic-card advancements has led to an increase in multiple monitor (multimon) use. Large displays offer users significant benefits and usability challenges. In this article the authors discuss those challenges along with novel techniques to address these issues.